2013
DOI: 10.1371/journal.pone.0071483
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiologic Characteristics of Norovirus GII.4 Sydney during Winter 2012–13 in Beijing, China following Its Global Emergence

Abstract: BackgroundLimited information is available on the molecular epidemiology of GII.4 Sydney-associated diarrhea in China in the winter of 2012–13 during the global epidemic associated with the emergence of GII.4 Sydney.MethodsFecal specimens collected from 171 diarrhea outpatients (one from each) between late October 2012 and the middle of March 2013 were examined for NoV by reverse transcription-polymerase chain reaction and sequences corresponding to both the NoV partial polymerase and partial capsid regions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
4
17
0
1
Order By: Relevance
“…Globally, GII.4 Sydney was first reported in Australia in March 2012; in China, it was first reported in Guangdong province in July 2012 (2) and then spread to many other provinces in China (8)(9)(10)(11). Data from August 2012-April 2013 monitored by the U.S. Centers for Disease Control and Prevention indicated that compared with other norovirus strains, GII.4 Sydney outbreaks disproportionally affected older persons, consistent with the observed predilection toward long-term care facilities (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Globally, GII.4 Sydney was first reported in Australia in March 2012; in China, it was first reported in Guangdong province in July 2012 (2) and then spread to many other provinces in China (8)(9)(10)(11). Data from August 2012-April 2013 monitored by the U.S. Centers for Disease Control and Prevention indicated that compared with other norovirus strains, GII.4 Sydney outbreaks disproportionally affected older persons, consistent with the observed predilection toward long-term care facilities (12).…”
Section: Discussionmentioning
confidence: 99%
“…Patients affected by GII.4 Sydney were more likely to have diarrheal illness and less likely to have vomiting, fever, and abdominal cramps. The surveillance data for diarrhea from October 2012 to March 2013 monitored by Peking University People's Hospital, a teaching hospital affiliated with Beijing University, showed that GII.4 Sydney caused severe fever, abdominal pain, and a higher frequency of diarrhea clinically compared with other norovirus infections (11). In the Shenzhen outbreak, the attack rates in the elderly and the staff were 15.9z and 23.2z, respectively, and the occurrence rates of bellyache and diarrhea were 86.5z and 67.6z, respectively; however, the occurrence rate of fever was only 2.7z.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A norovirus GI.1 monovalent VLP vaccine protected against illness and infection following challenge with homologous GI.1 Norwalk virus [11], prompting development of a bivalent GI.1/GII.4 VLP vaccine [12], as these 2 genogroups account for the majority of norovirus outbreaks [1317]. The GII.4 component is a consensus VLP derived from 3 naturally occurring GII.4 variants that induced broadly reactive antibody responses in animal studies and may induce a multivalent response against different genotypes [12].…”
mentioning
confidence: 99%
“…The most prevalent genotypes detected were still norovirus GII, accounting for 89.9% of identified strains [18] . Twenty-two of the 26 (84.6%) identified NoV strains clustered into GII.4 Sydney [19] , which causes severe fever, abdominal pain and higher diarrhea frequency clinically compared to other NoV infections, following its global emer--gency.…”
Section: Introductionmentioning
confidence: 99%